Research on the Breast Cancer Risk Factors and Possible Therapy - Gao, Yifei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This article introduces the benefits of public health that can be developed related policies through research to prevent or control pandemic or diseases. Cancer is now a major concern of public health worldwide. Research has been conducted to identify and solve the major problems for some types of cancer. This article gives some detailed information for one type of cancer, breast cancer. The third part of the article includes risk factors for breast cancer, which the unhealthy lifestyle is one of the possible risk factors includes alcohol intake, being overweight, that the likelihood of breast cancer development might grow. Also, the third part has the information that describe some of the genes that are commonly found in the breast cancer and some of could improve the breast cancer cells growth. For the fourth part, some possible and newly treatments will be mentioned. Through the assessment of risk factors, more people can be motivated to improve their lifestyles to decrease their risk, or to undergo genetic checking to identify whether have the high risk to diagnosis the breast cancer, which help people to know their risk and treat breast cancer earlier. The hormone therapy is one of the treatments which includes SERM that compete with estrogen and SERD directly block estrogen to bind to control the development of breast cancer cells. Hormonal therapy could contribute to controlling breast cancer recurrence, but people who use tamoxifen may develop resistance. In this way some targeted needs to be combined with hormone therapy.